The Impact of Mortgage Rates on Mortgage Refinancing - Ngwakwe, Collins C. (International Journal of Economics and Financial Issues, 2024)
Mortgages loans are vital for the acquisition of housing property and mortgage lending rates play an important role in mortgage market trends, borrowers, and lenders’ decisions. Objective: the aim of this paper is to evaluate the combined effect of current and previous mortgage rates on mortgage refinancing. Prior work: the paper inclines on the ontology of a single reality of the interaction between mortgage rates and mortgage refinancing with attendant epistemology that their interaction is measurable. Method: the paper adopts the positivist paradigm and a quantitative technique. It used data on the U.S. Mortgage Bankers Association (MBA) retrieved from the economic and financial database of Fusion Media. Data were analysed using the OLS technique. Novel Findings show that current-actual and previous mortgage rates have a significant positive effect on mortgage refinancing at p=0.05 and p=0.04 respectively. Significance: the findings have implication for mortgage lending and refinancing decisions for mortgage bankers (lenders), mortgage borrowers and policy makers. It also provides current academic study material for university business schools and for future researchers to apply the model used in this research for related expanded research. Value: The paper contributes a new model with two genres of mortgage rate (current mortgage rate and previous mortgage rate) and how these two types of mortgage rates influence mortgage refinancing.